Analisis Pencemaran Lingkungan sebagai Penyebab Banjir di Kawasan Jalan Pekapuran Kota Depok - Syamsa Azilla; Aprillia Intan Nur Cahya; Adrianus Rebon Piran (Intellektika : Jurnal Ilmiah Mahasiswa, 2026)
Environmental pollution is a common problem in cities and can increase the likelihood of flooding. The purpose of this study is to analyze environmental pollution as a cause of flooding in the Pekapuran Street area, Depok City. This study applies a descriptive method with a qualitative approach. Data were obtained through observation, documentation, and literature review. Based on the results of the study, it was found that the accumulation of household waste around the drainage channels causes obstruction of water flow, which triggers flooding during rain. In addition, the shallow, mud-filled, and poorly maintained drainage conditions increase the risk of flooding. Low levels of public awareness of environmental cleanliness are also factors that exacerbate the condition. This study concludes that flooding on Pekapuran Street is influenced not only by high rainfall, but also by environmental pollution and a suboptimal drainage system. Based on this, better waste management and drainage maintenance are needed to minimize the risk of flooding in the area.